2023
DOI: 10.2196/40922
|View full text |Cite
|
Sign up to set email alerts
|

User-Chatbot Conversations During the COVID-19 Pandemic: Study Based on Topic Modeling and Sentiment Analysis

Abstract: Background Chatbots have become a promising tool to support public health initiatives. Despite their potential, little research has examined how individuals interacted with chatbots during the COVID-19 pandemic. Understanding user-chatbot interactions is crucial for developing services that can respond to people’s needs during a global health emergency. Objective This study examined the COVID-19 pandemic–related topics online users discussed with a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The chatbots are increasingly showing several applications in the health domain . Diverse keywords [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] are associated with the concept of the chatbot in healthcare; among the most frequent we find: patient engagement, clinical support, mental health, health monitoring, patient education, appointment scheduling, symptom checking, chronic disease management, triage, remote monitoring, telemedicine, health coaching and emergency response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chatbots are increasingly showing several applications in the health domain . Diverse keywords [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] are associated with the concept of the chatbot in healthcare; among the most frequent we find: patient engagement, clinical support, mental health, health monitoring, patient education, appointment scheduling, symptom checking, chronic disease management, triage, remote monitoring, telemedicine, health coaching and emergency response.…”
Section: Resultsmentioning
confidence: 99%
“…Chatbots can be used in several fields in the health domain [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]: (a) As a tool for answering frequently asked questions [ 39 ]; (b) For the collection of data and patient details [ 39 , 42 , 43 ]; (c) To support patients finding a doctor or a specific service, on managing appointments, and on the medication dispensing procedure [ 42 ]; (d) As an interactive guide to the management of self-assessment and symptom control [ 39 , 42 ]; (e) As a tool to guide an interactive triage, applicable in the case of an emergency as well [ 36 ]; (f) In telehealth, digital health applications, and remote monitoring [ 37 , 39 , 40 , 42 , 43 ]. (g) In the learning process, in the construction of scientific knowledge and in supporting scientific dissemination [ 35 , 38 ]; (h) In mental health applications [ 37 , 38 ]; (i) For physical wellness and health coaching [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…We must admit that the chatbot is extremely popular, as it is very user-friendly, and patients as users may focus more on the benefits of convenience and efficiency, rather than the reliability and accuracy of the tool (Chin et al, 2023 ). ChatGPT also presents an air of authority and so sounds rather trustworthy.…”
Section: Chatgpt As a Disruptive Technologymentioning
confidence: 99%
“…Chin et al [15] analyzed 19,782 conversation utterances that are related to COVID-19 which cover different countries between 2020 and 2021. The authors identified chat topics (NLP) methods to analyze the emotional sentiments.…”
Section: Sentiment Analysis Based On Social Media Posts During Covid-19mentioning
confidence: 99%